A potential toolbox for improving the accessibility process in historic villages - Luigi Biocca (Built Heritage)
Abstract Accessibility, defined as inclusiveness in the access to and use of the built environment, is a complex process that involves several factors from multidisciplinary sectors. Thus, it is a prominent topic for heritage and cultural, tourist, social and economic regeneration and exploitation. Many historic villages in Italy offer potential heritage value for greater tourism attractiveness. This paper suggests a toolbox for differentiated accessibility levels. A case study identifies an analysis process of four activities, leading to a methodological scheme for determining accessibility options. 1) Direct preliminary analysis—walk-through and inspection—of the accessibility situation; 2) Selection of heritage characteristics and values for tourist attractiveness; 3) Community participation through questionnaires, interviews and walk-through; and. 4) Definition of a route system with different accessibility levels for human needs and expectations. The toolbox scheme can guide the accessibility process and steps towards alternative solutions on the basis of selected cultural values.